Investigation of criminal offenses committed under martial law: forensic and procedural aspects - Korniyenko, Mykhaylo; Dubivka, Iryna; Nikitenko, Viktor; Myrovska, Anna (Universidad Hemisferios, 2025)
The article examines the forensic and procedural aspects of the investigation of criminal offenses committed under martial law. In that sense, particular attention is paid to the transformation of law enforcement practice and the adaptation of the criminal procedural legislation of Ukraine to new security challenges; the issues of admissibility of evidence in national and international jurisdictions are analyzed, in particular in the context of interaction with the International Criminal Court (ICC); the advisability of making amendments to the Criminal Procedure Code (CPC) of Ukraine in terms of detailing international cooperation in the investigation of war crimes, improving the procedure for clarifying the rights of participants in the criminal process during individual investigative (search) actions is indicated, based on the experience of the functioning of individual legal systems in international conflicts; the emphasis is placed on the need to harmonize the criminal procedural legislation of Ukraine with the provisions of international humanitarian law and improving the mechanisms of interdepartmental and international investigative cooperation; and the need for legal regulation of the use of modern digital and analytical tools in forensics is substantiated, which also requires increasing technical awareness, acquiring new skills in working with analytical methods and products, and establishing constant close cooperation with other entities of documentation and investigation. The results of the study have practical significance for increasing the efficiency of the investigation of crimes committed during the armed conflict, while ensuring compliance with human rights and the principles of the rule of law.